Staple line leak with peritonitis after laparoscopic sleeve gastrectomy – a solution in one to six steps - Petr Špička (Videosurgery and Other Miniinvasive Techniques)
Introduction: Laparoscopic sleeve gastrectomy (LSG) is one of the most efficient bariatric interventions in morbidly obese patients. The most severe risk of this procedure seems to be the staple line leak, and the management of this complication can be very arduous. Aim : To share our experience in managing the staple line leak after LSG and to help to find the best procedure that should be preferred. Material and methods : In the 2010–2015 period we performed 223 LSG, with about 5 demonstrating severe complications – two patients with severe bleeding requiring revision surgery, and three patients with resection surface leak. Results : We always primarily treated the staple line leak with a laparoscopic revision. Once the fistula did not spontaneously close after this treatment. A series of other methods were then indicated for this patient and only the sixth one resulted in the desirable therapeutic success. At first, our team opted for laparoscopic revision with drainage. The next procedure involved applying Ovesco and Boston clips. As a third method we performed abscess drainage through a nasobiliary tube inserted via gastroscopy. Due to failure we performed the second laparoscopic revision with staple line resuture, the next intervention was an open revision with fistula excision and suture, and finally we opted for the application of a self-expanding metallic stent, which proved to be definitely curative. Conclusions : Without any guidelines it is very difficult to determine the right procedure addressing the staple line leak after LSG. It depends mainly on the clinician’s experience and is lengthy and often untraditional.